2020
DOI: 10.3390/agronomy10030450
|View full text |Cite
|
Sign up to set email alerts
|

Differential Aquaporin Response to Distinct Effects of Two Zn Concentrations after Foliar Application in Pak Choi (Brassica rapa L.) Plants

Abstract: Zinc (Zn) is considered an essential element with beneficial effects on plant cells; however, as a heavy metal, it may induce adverse effects on plants if its concentration exceeds a threshold. In this work, the effects of short-term and prolonged application of low (25 µM) and high (500 µM) Zn concentrations on pak choi (Brassica rapa L.) plants were evaluated. For this, two experiments were conducted. In the first, the effects of short-term (15 h) and partial foliar application were evaluated, and in the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Other studies reported similar findings for Pu’er and black tea [ 27 , 36 ]. Therefore, Cr contamination in tea leaves needs special attention and prevention measures, such as spraying leaf tissue control agents to reduce Cr absorption in tea leaves [ 37 ] and finding tea varieties with a reduced risk of Cr accumulation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported similar findings for Pu’er and black tea [ 27 , 36 ]. Therefore, Cr contamination in tea leaves needs special attention and prevention measures, such as spraying leaf tissue control agents to reduce Cr absorption in tea leaves [ 37 ] and finding tea varieties with a reduced risk of Cr accumulation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…(ii) (Zn solutions: 3 mL per plant, containing zinc sulphate at concentrations of 50, 100, 500 or 1000 µM, with 0.1% non-ionic, organo-silicon surfactant, were sprayed onto the leaves three times a week for one week. As we had found previously that 25 µM zinc sulphate did not produce any negative effect on plant biomass [32], in this experiment, to check the levels of toxicity, the lowest concentration was 50 µM.…”
mentioning
confidence: 73%
“…The regulatory influence of HMs on AQP activity and expression has been validated in several plants, like Hgstressed Pisum sativum (Beaudette et al, 2007), Cu-stressed Mesembryanthemum crystallinum (Kholodova et al, 2011), arsenic [As (III)] exposed Brassica juncea (Srivastava et al, 2013), HMs (Zn 2+ , Pb 2+ , Cd 2+ , and Hg 2+ ) stressed Allium cepa that accounted to metal-induced drop in water permeability in the order of Hg 2+ > Cd 2+ > Pb 2+ > Zn 2+ (Przedpelska-Wasowicz andWierzbicka, 2011), Zn-stressed poplar (Ariani et al, 2019), and Brassica rapa (Fatemi et al, 2020). Multiple reports validate the significance of AQP activity as efflux transporters that excrete HMs out of the cellular space (Vats et al, 2021).…”
Section: Heavy Metal Stressmentioning
confidence: 99%